2017
DOI: 10.1111/ajt.14419
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Protease Inhibitor–Based Anti-Retroviral Therapy on Outcomes for HIV+ Kidney Transplant Recipients

Abstract: Excellent outcomes have been demonstrated among select HIV-positive kidney transplant (KT) recipients with well-controlled infection, but to date, no national study has explored outcomes among HIV+ KT recipients by antiretroviral therapy (ART) regimen. Intercontinental Marketing Services (IMS) pharmacy fills (1/1/01-10/1/12) were linked with Scientific Registry of Transplant Recipients (SRTR) data. A total of 332 recipients with pre- and posttransplantation fills were characterized by ART at the time of transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 25 publications
2
43
0
1
Order By: Relevance
“…Interestingly, this favorable effect on graft survival is in contrast to results from a recent study analyzing SRTR data in 332 recipients, which found a 1.8 and 1.9‐fold increased risk in graft loss and death, respectively, in PI‐based regimens compared to non‐PI based regimens . Although the SRTR study contains a larger cohort than our patient population, one cannot discount the potential selection biases and unaccounted confounders in this type of study, which analyzed retrospective data from multiple centers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, this favorable effect on graft survival is in contrast to results from a recent study analyzing SRTR data in 332 recipients, which found a 1.8 and 1.9‐fold increased risk in graft loss and death, respectively, in PI‐based regimens compared to non‐PI based regimens . Although the SRTR study contains a larger cohort than our patient population, one cannot discount the potential selection biases and unaccounted confounders in this type of study, which analyzed retrospective data from multiple centers.…”
Section: Discussionmentioning
confidence: 99%
“…to results from a recent study analyzing SRTR data in 332 recipients, which found a 1.8 and 1.9-fold increased risk in graft loss and death, respectively, in PI-based regimens compared to non-PI based regimens. 16 Although the SRTR study contains a larger cohort than our patient population, one cannot discount the potential selection biases and unaccounted confounders in this type of study, which analyzed retrospective data from multiple centers. Specifically, of the patients transplanted in the study's eligible timeframe, approximately 40% of patients were excluded due to missing post-transplant fill data.…”
Section: Interestingly This Favorable Effect On Graft Survival Is Inmentioning
confidence: 99%
See 2 more Smart Citations
“…This drug‐drug interaction is thought to have contributed to several cases of graft rejection, with case reports dating back to the late 1990s . Sawinski, et al found a 1.8‐fold increased risk of allograft loss in a national survey of renal transplant patients on a PI regimen . The American Society of Transplant (AST) Infectious Disease Community of Practice guidelines recommend caution with use of PI‐containing regimens due to these concerns …”
Section: Introductionmentioning
confidence: 99%